Cerium and Ytterbium Codoped Halide Perovskite Quantum Dots: A Novel and Efficient Downconverter for Improving the Performance of Silicon Solar Cells. Issue 42 (29th September 2017) - Zhou, Donglei; Liu, Dali; Pan, Gencai; Chen, Xu; Li, Dongyu; Xu, Wen; Bai, Xue; Song, Hongwei
Abstract: Quantum cutting can realize the emission of multiple near‐infrared photons for each ultraviolet/visible photon absorbed, and has potential to significantly improve the photoelectric conversion efficiency (PCE) of solar cells. However, due to the lack of an ideal downconversion material, it has merely served as a principle in the laboratory until now. Here, the fabrication of a novel type of quantum cutting material, CsPbCl1.5 Br1.5 :Yb 3+, Ce 3+ nanocrystals is presented. Benefiting from the larger absorption cross‐section, weaker electron–phonon coupling, and higher inner luminescent quantum yield (146%), the doped perovskite nanocrystals are successfully explored as a downconverter of commercial silicon solar cells (SSCs). Noticeably, the PCE of the SSCs is improved from 18.1% to 21.5%, with a relative enhancement of 18.8%. This work exhibits a cheap, convenient, and effective way to enhance the PCE of SSCs, which may be commercially popularized in the future. Abstract : Cerium and ytterbium codoped halide perovskite quantum dots display an efficient near‐infrared emission with inner luminescent quantum yield of 146%. The quantum dots are explored to enhance the performance of silicon solar cells with a relative enhancement of 18.8%.